STUDI KESESUAIAN PENERAPAN STANDAR LINGKUNGAN PERUMAHAN SEDERHANA SEHAT DI KOTA SERANG - Ria Nurul Fitri; Soedwiwahjono Soedwiwahjono; Rufia Andisetyana Putri (Universitas Sebelas Maret Surakarta, 2015)
Serang city is the Capital City of Banten Province. As the time goes by, the population increases and the poor people needs an access to have a home. There are two housing environments, which is called “simple healthy housing environment” to help the poor people ,which are Banten Indah Permai and Bumi Serang Timur, but the condition is the housing environments are lack of infrastructures and facilities. This problem makes a question how the suitability of simple healthy housing environment in Kota Serang is. The suitability study of simple healthy housing environment in Serang city is done by using scoring method analysis to count the suitability of the simple healthy housing environment standards as the output and perception of the people inside the housing environment as the outcome of this simple healthy housing environment. Descriptive comparative analysis is used also to know how output and outcome can match each other in the housing environment. Final scoring result obtained that Banten Indah Permai has been classified as suit in output because of the 58 score , but Bumi Serang Timur is not suit in output because it has 55 score. In outcome scoring, Banten Indah has been classified as suit in outcome for the 76,94 score, and also for Bumi Serang Timur has 75,68 for the outcome score. With comparative analyisis, this study also obtained that there are many infrastructure and facilities in housing environment which are not give the outcome as usual the housing environment gives. Keywords: simple healthy housing, suitability, scoring, environment,